Graphical User Interface for Adaptive Human-Robot Interaction Design in Educational Activities Creation - Tozadore, Daniel; Romero, Roseli (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2018: Anais do XXIX Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/cbie.sbie.2018.605, 2018)
Robots and interactive devices are being successfully applied in education to increase the students cognitive experience and, consequently, their learning rate. However, there is a lack of social robots with adaptive skills that can be easily programmed. In this paper, a Graphical User Interface to create, perform and evaluate educational activities with autonomous robots is presented. The interface runs in a system that provides adaptation and personalization through open source techniques for autonomous analysis and recognition of speech, focus deviation and facial emotion. During the activity execution, the adaptive algorithm detects student’s body signals and verbal responses to adapt the addressed content to harder or easier questions. After creating and running an activity, all sessions’ evaluation and information can be accessed for visual analysis, as well as students’ preferences throughout the interaction.